Testing a Holistic Framework of Early Care and Education and K-12 Leaders' Working Conditions and Well-Being - Timothy G. Ford; Kyong-Ah Kwon; Alyson L. Lavigne; Tom McHugh (SAGE Publishing, 2024)
The importance of leadership for key educational outcomes is well documented, yet leaders' working conditions and well-being have received considerably less attention, particularly in the early care and education (ECE) sector. Job-Demands-Resources (JD-R) theory was used to develop a holistic conceptualization of leader well-being for the purpose of examining the associations among various job demands, resources, and well-being (i.e., physical, psychological, and professional well-being) for leaders of birth to 12th grade (B-12). We tested our conceptual model via structural equation modeling (SEM) with over 2,000 ECE and K-12 building leaders across the United States. We found substantially stronger effects between job demands and well-being relative to job resources and well-being, though resources were found to be directly associated with professional well-being. Further, our tested model was similar for both ECE and K-12 leaders. Overall findings suggest that a reduction in demands-not just increased resources-is needed to ensure improved leader well-being.